2012
DOI: 10.1093/carcin/bgs358
|View full text |Cite
|
Sign up to set email alerts
|

Src kinase is a direct target of apigenin against UVB-induced skin inflammation

Abstract: Apigenin, a flavonoid abundant in various vegetables and fruits, including parsley and onions, has been reported to possess anticarcinogenic effects. However, the direct molecular target of apigenin and its chemopreventive effect on ultraviolet (UV)-induced skin inflammation are not understood fully. Herein, we examined the anti-inflammatory effect of apigenin and its associated mechanisms in JB6 P+ cell line and SKH-1 hairless mouse model. Apigenin inhibited UVB-induced cyclooxygenase-2 (COX-2) expression, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 42 publications
2
48
0
1
Order By: Relevance
“…Therefore, apigenin may be less potent than quercetin due to lower affinity caused by omission of the C ring C-10 hydroxyl from the structure of the flavone. Apigenin may be more selective for Src than for Lyn, Fyn and Hck, as previous studies demonstrate; in in vitro pull-down assays the flavone binds Src in an adenosine triphosphate-competitive manner[48].Within the ATP binding pocket of Lyn (Figure 5E. and 5F.…”
mentioning
confidence: 59%
“…Therefore, apigenin may be less potent than quercetin due to lower affinity caused by omission of the C ring C-10 hydroxyl from the structure of the flavone. Apigenin may be more selective for Src than for Lyn, Fyn and Hck, as previous studies demonstrate; in in vitro pull-down assays the flavone binds Src in an adenosine triphosphate-competitive manner[48].Within the ATP binding pocket of Lyn (Figure 5E. and 5F.…”
mentioning
confidence: 59%
“…Previous studies have also reported multiple JAK2 inhibitors that maintained or increased the phosphorylation levels of JAK2 (44,45). In addition, inhibitors for other kinases have been shown to not affect the phosphorylation levels of the target kinase, whereas the activity was inhibited by the compounds (51)(52)(53). A possible explanation might be that a negative feedback pathway occurs after inhibition of JAK2 such that a hyperactivated upstream kinase could increase the phosphorylation level.…”
Section: Discussionmentioning
confidence: 97%
“…We adopted the excessive sUV exposure‐related skin inflammation model, as over‐exposure of skin to UV is a physiological stimulator of skin inflammation (Lopes & Mcmahon, 2016). The JB6 P+ cell line is an optimized model for studying skin inflammation owing to its sensitivity to inflammatory enhancers such as UV, EGFR, and 12‐O‐tetradecanoylphorbol‐13‐acetate (TPA) (Byum et al., 2013; Chen et al., 2001). We found that COX‐2 expression induced by sUV irradiation is dose‐dependently attenuated by RPE treatment.…”
Section: Discussionmentioning
confidence: 99%